2006
DOI: 10.1038/nm1441
|View full text |Cite
|
Sign up to set email alerts
|

Connexin37 protects against atherosclerosis by regulating monocyte adhesion

Abstract: A genetic polymorphism in the human gene encoding connexin37 (CX37, encoded by GJA4, also known as CX37) has been reported as a potential prognostic marker for atherosclerosis. The expression of this gap-junction protein is altered in mouse and human atherosclerotic lesions: it disappears from the endothelium of advanced plaques but is detected in macrophages recruited to the lesions. The role of CX37 in atherogenesis, however, remains unknown. Here we have investigated the effect of deleting the mouse connexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
280
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(287 citation statements)
references
References 29 publications
3
280
1
3
Order By: Relevance
“…Our in vivo and in vitro results indicate that KCs express at least Cx43 but they might also express other Cx types as other macrophagic cells do. For example, monocyte/ macrophages also express Cx37 (21) and Cx45 (19) and microglia also express Cx36 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Our in vivo and in vitro results indicate that KCs express at least Cx43 but they might also express other Cx types as other macrophagic cells do. For example, monocyte/ macrophages also express Cx37 (21) and Cx45 (19) and microglia also express Cx36 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a critical role for Cx43 has been reported in human saphenous vein during the development of intimal hyperplasia (Deglise et al 2005) and restenosis (Plenz et al 2004) and Cx43 decreases smooth muscle cell proliferation and limits neointima formation after vascular injury (Chadjichristos et al 2006). Conversely, regeneration of the endothelium following carotid artery injury in rats, a process essential for wound healing, is associated with increasing expression of Cx37, Cx40, and Cx43 (Yeh et al 2000).…”
Section: Sex Differences In Vessel Repairmentioning
confidence: 99%
“…more than one type of connexin) cell communication and, in particular, has been attributed to gap junctions comprised Cx40 and Cx37 (Zahler et al 2003) and Cx43 (Parthasarathi et al 2006). More recently, the functional consequences of this inhibitory activity have been highlighted in APOE KO mice (a model of atherosclerosis) also deleted for Cx37, where lesion formation was substantially enhanced (Wong et al 2006). Several studies clearly demonstrate that the expression of Cx37, Cx40, and Cx43 are all regulated by estrogen (Di et al 2001, Punyadeera et al 2005, and it is likely that this regulation, to some extent, underlies the effects of female sex hormones on leukocyte recruitment, such that the enhancement of expression of the gap junctions may in part mediate the decreased inflammatory cell recruitment evident in female animal models of inflammation.…”
Section: Sex Differences In Leukocyte Recruitmentmentioning
confidence: 99%
“…The cell gap junction is an important channel for message exchange between cells (20). In 2006, Wong et al found that Cx37 knockout mononuclear phagocytes adhered to the endothelium more strongly than Cx37-deficient cells (21). This characteristic was associated with the adenosine triphosphate (ATP) release between cells.…”
Section: Discussionmentioning
confidence: 99%